Saccharomyces boulardii Allows Partial Patients to Avoid Reusing Bismuth Quadruple for Helicobacter pylori Rescue Therapy: A Single-Center Randomized Controlled Study - Qu, Peng; Liu, Xiaoming; Xia, Xiujuan; Xie, Xiaoran; Luo, Ju; Cheng, Sha; Chi, Jingshu; Liu, Peng; Li, Huan; Zhao, Wenfang; Yang, Huihao; Xu, Canxia (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Background: The increasing rate of drug resistance often leads to eradication failure of pathogens, thus necessitating rescue therapy. Thus, the exploration of new rescue therapeutic regimens is important. In this study, we aim to observe the efficacy and adverse events of the rescue treatment of Helicobacter pylori (H.pylori) with Saccharomyces boulardii (S.boulardii) alone. Methods: One hundred patients were randomly divided into a study group and a control group. The study group (n=50) underwent two stages of treatment, Patients started with S.boulardii monotherapy for 2 weeks, then, after stopping the drug for 4 weeks， patients who were still positive for H. pylori continued with bismuth quadruple therapy. In the control group (n=50), patients were observed for 6 weeks and were not treated with any gastric drugs or antibiotics. Those who were still positive for H. pylori continued with bismuth quadruple therapy containing doxycycline and furazolidone. Results: In the rescue treatment group, the ITT (intent-to-treat ) analysis of the eradication rate in the first phase of treatment in the study group and control groups produced values of was 28.0% and 2.0%, respectively, and 30.4% and 2.1% in the PP (per-protocol) analysis. (p<0.001). For the total treatment effect, the ITT analysis of the eradication rate produced values of 78.0% and 80.0% in the study group and the control group, (p=0.81), respectively, as well as values of 90.7% and 88.9% in the PP analysis, respectively (p=1.0). The incidence of adverse events was lower in the group treat with S. boulardii alone（n=2) than in the bismuth quadruplet group（n=4), but there was no statistical difference(p=0.68). Conclusion: Both two regimens achieved high eradication rates for rescue therapy, while treatment with S. boulardii alone was shown to eradicate H. pylori in some patients during rescue therapy, thereby exempting them from the reuse of antibiotics.Thus, it may be utilized as a pre-treatment for the rescue therapy of H.pylori, pending as one of the options for rescue therapy.